Pathways to effective surgical coverage in a lower-middle-income country: A multiple methods study of the family physician-led generalist surgical team in rural Nepal - Ollie Ross; Rabina Shakya; Rishav Shrestha; Shristi Shah; Amita Pradhan; Rahul Shrestha; Pushkar Bhandari; Becky Paris; Kashim Shah; Anil Shrestha; Mark Zimmerman; Hannah Henrikson; et al. (Public Library of Science (PLoS), 2023)
The Lancet Commission on Global Surgery (LCoGS) recommends using specialist surgical workforce density as one of 6 core indicators for monitoring universal access to safe, affordable surgical and anaesthesia care. Using Nepal as a case study, we explored the capacity of a generalist workforce (led by a family physician or MD general practitioner and non-physician anaesthetist) to enable effective surgical delivery through task-shifting. Using a multiple-methods approach, we retrospectively mapped essential surgical care and the enabling environment for surgery in 39 hospitals in 25 remote districts in Nepal and compared it with LCoGS indicators. All 25 districts performed surgery, 21 performed Caesarean section (CS), and 5 met at least 50% of district CS needs. Generalist surgical teams performed CS, the essential major operation at the district level, and very few laparotomies, but no operative orthopaedics. The density of specialist Surgeon/Anaesthesiologist/Obstetrician (SAO) was 0·4/100,000; that of Generalist teams (gSAO) led by a family physician (MD General Practitioners-MDGP) supported by non-physician anaesthetists was eight times higher at 3·1/100,000. gSAO presence was positively associated with a two-fold increase in CS availability. All surgical rates were well below LCoGS targets. 46% of hospitals had adequate enabling environments for surgery, 28% had functioning anaesthesia machines, and 75% had blood transfusion services. Despite very low SAO density, and often inadequate enabling environment, surgery can be done in remote districts. gSAO teams led by family physicians are providing essential surgery, with CS the commonest major operation. gSAO density is eight times higher than specialists and they can undertake more complex operations than just CS alone. These family physician-led functional teams are providing a pathway to effective surgical coverage in remote Nepal.